Vertical Extrusion Cryo(bio)printing for Anisotropic Tissue Manufacturing. Issue 12 (5th February 2022) - Luo, Zeyu; Tang, Guosheng; Ravanbakhsh, Hossein; Li, Wanlu; Wang, Mian; Kuang, Xiao; Garciamendez‐Mijares, Carlos Ezio; Lian, Liming; Yi, Sili; Liao, Junlong; Xie, Maobin; Guo, Jie; et al.
Abstract: Due to the poor mechanical properties of many hydrogel bioinks, conventional 3D extrusion bioprinting is usually conducted based on the X – Y plane, where the deposited layers are stacked in the Z ‐direction with or without the support of prior layers. Herein, a technique is reported, taking advantage of a cryoprotective bioink to enable direct extrusion bioprinting in the vertical direction in the presence of cells, using a freezing plate with precise temperature control. Of interest, vertical 3D cryo‐bioprinting concurrently allows the user to create freestanding filamentous constructs containing interconnected, anisotropic microchannels featuring gradient sizes aligned in the vertical direction, also associated with enhanced mechanical performances. Skeletal myoblasts within the 3D‐cryo‐bioprinted hydrogel constructs show enhanced cell viability, spreading, and alignment, compared to the same cells in the standard hydrogel constructs. This method is further extended to a multimaterial format, finding potential applications in interface tissue engineering, such as creation of the muscle–tendon unit and the muscle–microvascular unit. The unique vertical 3D cryo‐bioprinting technique presented here suggests improvements in robustness and versatility to engineer certain tissue types especially those anisotropic in nature, and may extend broad utilities in tissue engineering, regenerative medicine, drug discovery, and personalized therapeutics. Abstract : A vertical 3D cryo‐bioprinting technique is reported, which concurrently allows the user to create freestanding filamentous constructs containing interconnected, anisotropic microchannels featuring gradient sizes aligned in the vertical direction, also associated with enhanced mechanical performances. This method is further extended to a multimaterial format, finding potential applications in interface tissue engineering, regenerative medicine, drug discovery, and personalized therapeutics.